Addition of central obesity criteria increases the prevalence of clinical obesity in women with polycystic ovary syndrome - Islam, Md. Rafayel; Morshed, Md. Shahed; Banu, Hurjahan; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: The Lancet Diabetes & Endocrinology Commission 2025 has recommended a newer definition and diagnostic criteria for clinical obesity. The impact of this newer definition has not been evaluated among women with polycystic ovary syndrome (PCOS). Objectives: To determine and compare the frequency of obesity with previous and newer definitions among women with PCOS Methods: This cross-sectional study included 765 adult women [age (years): 23.8 ±4.5; BMI (kg/m2): 27.7 ± 5.3; mean ± SD] with (newly diagnosed/ untreated for at least three months) PCOS based on the Rotterdam criteria from a University hospital in South Asia. Participants’ height, weight, waist circumference (WC), and hip circumference were measured. Body mass index (BMI), waist/hip ratio (WHR), and waist/height (WHtR) were calculated. Three BMI cut-offs of 23.0, 25.0, and 27.5 kg/m2 were considered. The cut-off of WC, WHR, and WHtR were 80 cm, 0.85, and 0.5, respectively. The following two criteria were used to define obesity: i) BMI + WC/WHR/WHtR, and ii) any two from WC, WHR, & WHtR regardless of BMI. Additionally, blood pressure (BP), glycemic status (fasting & OGTT glucose, HbA1C), and lipid profile (triglyceride & HDL-cholesterol) were considered for clinical obesity. Results: Using the BMI cut-offs of 23, 25, and 27.5 kg/m2, the prevalence of obesity was 82.1%, 67.5%, and 47.1%, respectively. Using the current definition, the prevalence of obesity was 80.5%, 81.4%, and 79.4%, respectively, for the three BMI cut-offs, resulting in increases in prevalence of 1.8%, 20.7%, and 68.6%, respectively. All participants with obesity had clinical obesity, as the presence of PCOS indicates an ongoing illness. Besides, a significant portion had arterial hypertension, dysglycemia, and lipid abnormalities. Conclusions: The Presence of higher central obesity (WC, WHR, WHtR) than generalized obesity (BMI) paradoxically increased the diagnosis of clinical obesity among South-Asian women with PCOS. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2024;3(Suppl 1): S64]